Trace elemental analysis of mitral valves by EDXRF. Issue 1 (2008) - Ates Ates, A. A.; Simsek Simsek, O. O.; Ertugral Ertugral, B. B.; Ertugrul Ertugrul, M. M.
Abstract : The elemental analysis of mitral valves from 12 patients with rheumatic mitral valve disease was performed using radioisotope excited energy dispersive X-ray fluorescence (EDXRF) technique. An annular 50 mCi 55 Fe radioactive source was used for excitation of characteristic K X-rays of the trace elements in the samples. A high resolution Si(Li) detector, which has a 160 eV full width at half maximum for 5.9 keV photons, was used for intensity measurements. Concentrations of the elements P, S, K and Cl in the mitral valve samples were determined by using standard addition method. Deficiencies or excesses of these trace elements cause the valves to run irregularly. Abnormal value of these elements may also result in rheumatic valve disease.